신경독성 조개류 중독 3례 - 고영길; Young Gil Ko; 안지영; Ji Young Ahn; 류석용; Seok Yong Ryu; 이상래; Sang Lae Lee; 조석진; Suk Jin Cho; 김미란; Mi Ran Kim (대한임상독성학회지, 2006)
Neurotoxic shellfish poisoning (NSP) can result from eating filter-feeding shellfish carrying brevetoxins produced by the marine dinoflagellate Krenia brevis (formally Gymnodinium breve). Brevetoxins enhance sodium entry into cells via voltage-sensitive sodium channels and have an excitatory effect. The incubation period is three hours (range 15 minutes-18 hours). NSP is characterized by gastroenteritis combined with neurologic symptoms. Gastrointestinal (GI) symptoms include abdominal pain, nausea, diarrhea and burning pain in the rectum. Neurologic symptoms are paresthesia, reversal of hot and cold temperature sensation, myalgia, headache, vertigo, and ataxia. Other symptoms may include malaise, tremor, dysphagia, bradycardia, decreased reflexes, dilated pupils, seizure, and coma. The health problem caused by K. breviscan be associated with a red tide bloom. We encountered 3 cases of neurotoxic shellfish poisoning. They all presented with GI and neurologic symptoms andrecovered after conservative treatment.